Mediating role of organized sports participation on the relationship between body fatness and arterial wall thickness among adolescents: ABCD Growth Study - Torres, Wésley [UNESP]; Maillane-Vanegas, Santiago [UNESP]; Urban, Jacqueline Bexiga [UNESP]; da Silva, Danilo Rodrigues Pereira; Oliveira, Ricardo Santos; Haapala, Eero A.; Fernandes, Rômulo Araújo [UNESP] (Springer Nature, 2025)
Background: Participation in sports is the main manifestation/subdomain of physical exercise in adolescents and affects cardiovascular health in different ways. Objectives: To analyze the relationship between body fatness and arterial wall thickness as well as the mediating role of sports participation in this relationship among adolescents. Methods: This cross-sectional study is linked to the ABCD-Growth Study conducted in Presidente Prudente, Brazil. The study sample included 402 adolescents (275 boys and 127 girls) aged 11–17 years recruited from schools (non-sport group) and sports clubs (sports group). Sex-stratified multivariate model was created using structural equation modelling (SEM) with carotid (CIMT) and femoral arterial wall thickness (FIMT) as dependent variables were assessed by an ultrasound device. Body fatness percentage (BF) as the independent variable and was assessed by whole-body dual-energy X-ray absorptiometry, and sports participation as a moderator was assessed by face-to-face interviews. The maturity offset and dyslipidemia were treated as confounders in the mediation models. Results: In girls, body fatness was positively associated with FIMT (r = 0.210 [95%CI: 0.035; 0.372]) but not with CIMT (r= -0.148 [95%CI: -0.314; 0.027]), whereas sports participation was not associated with vascular structure. In boys, body fatness was inversely related to CIMT (r= -0.285 [95%CI: -0.390; -0.172]) and positively to FIMT (r = 0.129 [95%CI: 0.011; 0.244]), whereas sports participation was inversely related to FIMT (r= -0.142 [95%CI: -0.256; -0.024]). Among boys, sports participation mediated 7.4% of the relationship between body fatness and FIMT, and the association between body fatness and FIMT remained significant (r = 0.168 [95%CI: 0.037; 0.299]). Conclusions: Sports participation mediates the relationship between BF and arterial thickness in adolescent boys.
Keywords: Adiposity; Adolescents; Physical activity; Risk factors